Analysis Of The Aeroacoustic Performance Of Twin Propellers In Hover By Using The Cira-Cusano Test Rig - Visingardi, A.; Barbarino, M.; De Gregorio, F.; Greco, L.; Testa, C.; Zaghi, S.; Yin, J.; Reboul, G.; Cavalli, A.; Granata, D.; Abergo, L.; Guardone, A.; et al. (My University, 2024)
The present work illustrates numerical-experimental aeroacoustic investigations of single and twin co-rotating propeller configurations in hover flight. The activity was aimed at evaluating the effect of the inter-axis distance between the twin-propellers, the phase angle, and the sense of rotation of the secondary propeller, with respect to the main one, on the aeroacoustic properties of the examined configurations. Loads, PIV, and microphone measurements were jointly conducted by CIRA and Cusano University at CIRA. Specifically, aerodynamic and fluid dynamic measurements were performed in a laboratory environment, while acoustic measurements were conducted in a semi-anechoic chamber. The aerodynamic simulations were carried out by using solvers of different degrees of fidelity, from panel methods to URANS solvers, whereas the aeroacoustic analyses were all based on the Ffowcs Williams-Hawkings formulation. Both numerical and experimental results show that the loads acting on each propeller reduce passing from the single propeller to the twin-propeller configuration. This reduction decreases as the distance between the propellers increases. Negligible effects are produced on the loads by changing the phase angle and the sense of rotation of the secondary propeller. Conversely, the acoustics is more sensitive to these configurational changes: the noise produced by the twin propellers is higher than that of the single propeller, and the maximum is reached at the lower separation distance between the two propellers. De-phasing or changing the sense of rotation of the secondary propeller produces the highest increase in noise, with the maximum reached at the phase angle ? ? 60°.